Incidence and clinical features of viral sore throat among children in rural Haryana, India - Raghavan Parthasarathy (Journal of Family Medicine and Primary Care, 2020)
Background: Sore throat is one of the commonest symptoms that patients present to a primary care physician. We describe the epidemiology of sore throat and performance of an algorithm to predict viral sore throat in a part of India. Methods: Children below 10 years of age were followed in 4 villages of Haryana, India from Aug 2012 to Aug 2014 through weekly domiciliary visits by trained field workers who screened for symptoms of acute respiratory infection (ARI) including sore throat. Nasal and throat swabs were obtained from a random sample of sore throat cases by nurses and sent in appropriate transport media for real-time polymerase chain reaction for detection of viral nucleic acid. Incidence of sore throat and viral sore throat are reported as number of sore throat episodes per 1000 child-years (EPTCY) with 95% confidence-interval (CI). Symptoms, associated with viral sore throat were identified by logistic regression, combined into a clinical score and Receiver Operating Characteristic curve was plotted. Results: Over a two-year period, 3765 children were followed up for 5578 child years. 1069 episodes of sore throat were reported, and swabs were collected from 8% of the cases randomly. The incidence of sore throat and viral sore throat was 191.7 (95%CI: 180.5-203.6) and 60.1 (95%CI: 55.1-68.2) EPTCY, respectively. Fever (aOR 5.40,95%CI: 1.16-25.18) and running nose (aOR 10.16,95%CI: 1.01-102.42) was significantly associated with viral sore throat. The clinical score (fever, running nose, and headache) had an overall sensitivity of 86.2% (68.3-96.1%), specificity of 62% (47.2-75.3%) and AUC of 0.78 (0.67-0.87) in predicting viral sore throat. Conclusion: Viruses contributed to one-third of burden of sore throat and clinical score can be used in primary care settings to aid antibiotic prescription by physicians.